2013
DOI: 10.5455/aim.2013.21.257-260
|View full text |Cite
|
Sign up to set email alerts
|

Which Pharmaceutical Sales Representatives' Features do Slovenian Family Physicians Value?

Abstract: Introduction:One of the key strategies for marketing new drugs to physicians is personal selling by pharmaceutical sales representatives (PSRs).Goal:The aim of this study was to determine which features of PSR’s are most valued by Slovenian family physicians (FPs).Methods:We performed a cross-sectional observational postal survey in FPs. We sent the invitation for cooperation in the study to all Slovenian FPs working in family practices at the primary level of care (N = 895). Data was collected using a validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The pharmaceutical industries through their representatives are the main and most important sources of information of new drugs for the doctors. [2][3][4] Apart from the company representatives, non-peer-reviewed literature and the mass media could be other sources of information. Peer-reviewed literature or independent drug information sources are not significant to the doctors at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmaceutical industries through their representatives are the main and most important sources of information of new drugs for the doctors. [2][3][4] Apart from the company representatives, non-peer-reviewed literature and the mass media could be other sources of information. Peer-reviewed literature or independent drug information sources are not significant to the doctors at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32,37,40,44,45 ] With regard to high‐value promotional items, physicians who received honoraria or money to attend pharmaceutical symposia or as research support have been found to consider these appropriate gifts. [ 46,47 ] However, while some studies have reported physicians' beliefs in the appropriateness of perceiving MRs as sources of both education and funding, [ 37,40,48,49 ] other studies have documented sceptical attitudes towards these promotional activities. [ 38,50 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, it is apparent from the literature survey that MRs exert growing influence on the physicians' selection of particular drugs. For example, the location of medical practice have also been reported to influence how physicians perceive pharmaceutical marketing, thus affecting drug choices and future prescriptions [30]. Further, both private and public medical facilities have been reported to be potentially influenced by marketing tools employed by pharmaceutical companies, such as MR visits and face-to-face meetings [31,32].…”
Section: Effectiveness Of Pharmaceutical Companies' Promotional Tools In Influencing Physicians' Prescription Behaviormentioning
confidence: 99%
“…However, again, demographic factors were neglected in these studies, with the focus exclusively on promotional strategies. Further, Datta and Dave [4], reviewed prescriptions based on a free sample and found that physicians tend to use the same drug in subsequent prescriptions [30] meanwhile, reviewed the behavior among care beneficiaries that have financiallycapped drug prescriptions. The authors found that availability of free drug samples from pharmaceutical companies influences the behavior of medical beneficiaries and decisions for specific medications.…”
Section: Effectiveness Of Pharmaceutical Companies' Promotional Tools In Influencing Physicians' Prescription Behaviormentioning
confidence: 99%